2011
DOI: 10.1002/chem.201003119
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Selective Syntheses of 5‐Azaindoles through Zirconocene‐Mediated Multicomponent Reactions with Three Different Nitrile Components and One Alkyne Component

Abstract: 5-Azaindoles either with three different substituents at their 2-, 4-, and 6-positions or with two identical substituents at their 2- and 6-positions and a different one at the 4-position, were obtained in good to excellent isolated yields by a zirconocene-mediated multicomponent process. Each reaction involved four organic partners, comprising a Si-tethered diyne, one tBuCN component, and two (either different or identical) nitriles. All these four components were combined through the action of a Cp(2)Zr(II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 107 publications
0
10
0
4
Order By: Relevance
“…The Zr1–N2 distance of 2.199(2) Å is in the range of a single bond, and the N2 atom is only slightly pyramidalized (summation of bonding angles at N2 356.35°). The N1–C6 distance (1.251(3) Å) corresponds to an imine moiety 8h. The large distances of Zr1–C9 and Zr1–C8 (exceeds 3.0 Å) do not indicate a π interaction between Zr and the CC bond.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Zr1–N2 distance of 2.199(2) Å is in the range of a single bond, and the N2 atom is only slightly pyramidalized (summation of bonding angles at N2 356.35°). The N1–C6 distance (1.251(3) Å) corresponds to an imine moiety 8h. The large distances of Zr1–C9 and Zr1–C8 (exceeds 3.0 Å) do not indicate a π interaction between Zr and the CC bond.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that pyrroles were formed after hydrolysis of the zirconacycles. The Zr1–N1 distance of 2.024(2) Å indicates a σ bond between Zr and the sp 2 ‐hybridized imino N atom 8h. The Zr1–N2 distance of 2.199(2) Å is in the range of a single bond, and the N2 atom is only slightly pyramidalized (summation of bonding angles at N2 356.35°).…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11][12][13] However, few methods have been reported for azaindole synthesis based on multiple component reactions, which provide a divergent approach to functionalized azaindoles in a single step. [14][15][16][17] We recently reported the direct synthesis of 2-(aminomethyl)indoles 3 via copper-catalyzed domino threecomponent coupling and cyclization reactions of ethynylaniline 1 (Scheme 1). [18][19][20] The mechanism of this reaction involves the formation of the propargylamine intermediate 2 by Mannich-type three-component coupling of 1 with paraformaldehyde and a secondary amine, and subsequent copper-catalyzed intramolecular cyclization.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Surprisingly,M CRs in general have been rarely used to synthesize libraries of organometallics, [11][12][13] and to the best of our knowledge there are no reported examples of MCRs affording cesium-based organometallics.W ith an on-going interest in MCRs and molecular diversity generation, [14][15][16] our original intent was to use the Dieckmann condensation [17] on an Ugi adduct to access tetramic acids (pyrrolidine-2,4-diones;S cheme 1). [10] Surprisingly,M CRs in general have been rarely used to synthesize libraries of organometallics, [11][12][13] and to the best of our knowledge there are no reported examples of MCRs affording cesium-based organometallics.W ith an on-going interest in MCRs and molecular diversity generation, [14][15][16] our original intent was to use the Dieckmann condensation [17] on an Ugi adduct to access tetramic acids (pyrrolidine-2,4-diones;S cheme 1).…”
mentioning
confidence: 99%
“…Post-condensation strategies to manipulate IMCRs for molecular diversity generation are highly productive for the construction of avariety of heterocyclic scaffolds,particularly in al ibrary compatible manner. [10] Surprisingly,M CRs in general have been rarely used to synthesize libraries of organometallics, [11][12][13] and to the best of our knowledge there are no reported examples of MCRs affording cesium-based organometallics.W ith an on-going interest in MCRs and molecular diversity generation, [14][15][16] our original intent was to use the Dieckmann condensation [17] on an Ugi adduct to access tetramic acids (pyrrolidine-2,4-diones;S cheme 1).…”
mentioning
confidence: 99%